"Bear Witness" and "Build Legacies": Twentieth- and Twenty-First-Century Trans* Autobiography. (1st September 2016) - Rondot, Sarah Ray
ABSTRACT: After examining the historical tradition of twentieth-century autobiography by transsexual-identified writers, this article analyzes two contemporary life narratives: Alex Drummond's Grrl Alex: A Personal Journey to a Transgender Identity and Jennifer Finney Boylan's I'm Looking Through You: Growing Up Haunted: A Memoir . In contrast to earlier autobiographers, Drummond and Boylan representatively demonstrate a new era of trans* epistemology, which does not rely on the wrong-body model as the foundational aspect of trans* existence. Boylan remembers her haunting past, which inevitably leads her to seek medical intervention, while Drummond situates her self-actualized identity in opposition to medical discourse. Although their stories differ, their perspectives reflect similarly radical conceptions of gender. Because they narrate continuous subjects rather than subjects split between pre- and post-transition, Drummond and Boylan put forth a new way to understand and narrate trans* identity by exploring rather than justifying trans* experience.